FENOMENA SELEBRITAS SEBAGAI MODEL IKLAN DARI SUDUT PANDANG SUMBER PESAN - Kussudyarsana Kussudyarsana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2004)
At recent time, celebrities are easily found as product spokesperson. Marketer use celebrity inorder to their product to be recognized. To do that, the spokesperson must be credible. Source credibilityis very important, because the audience welcomes to credible spokesperson and reject incredible source.Two dimension of source credibility related to the celebrity, those are attractiveness and expertise.Research found expertise credibility more congruent to high involvement product, and attractiveness wasmatch to low involvement product.